2003
DOI: 10.1177/006996670303700103
|View full text |Cite
|
Sign up to set email alerts
|

A case of capital-rich under- development: The paradoxical consequences of successful transnational entrepreneurship from Mirpur

Abstract: No other District in Pakistan has seen a higher proportion of its population engage in transnational migration than Mirpur, and from nowhere else have a higher proportion of such migrants successfully established themselves in Britain. Yet despite the intensity of the trans-local linkages which have thereby been created, and the huge flow of remittance capital into a District which otherwise occupies a thoroughly marginalised position on the global periphery, in no way has this served to stimulate any kind of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 1 publication
3
39
0
Order By: Relevance
“…Other studies of South Asian migration, for example from Bangladesh (Gardner 1995), Pakistan (Ballard 2004;Erdal 2012), and Indian Gujarat (Ramji 2006) to the UK, and from Kerala, South India to the middle east (Osella and Osella 2000), reveal similar attempts to assert diasporic wealth, superiority and status through consumption practices within South Asia. These studies, and our own data, suggest that the meaning of home amongst diasporic groups can be significantly reprocessed as such groups become permanently settled in a primary lived home away from the outsource of migration and simultaneously exhibit their inclusion in a life (of conspicuous consumption) from which many remaining residents are excluded.…”
Section: Diaspora Spaces In Punjabmentioning
confidence: 89%
“…Other studies of South Asian migration, for example from Bangladesh (Gardner 1995), Pakistan (Ballard 2004;Erdal 2012), and Indian Gujarat (Ramji 2006) to the UK, and from Kerala, South India to the middle east (Osella and Osella 2000), reveal similar attempts to assert diasporic wealth, superiority and status through consumption practices within South Asia. These studies, and our own data, suggest that the meaning of home amongst diasporic groups can be significantly reprocessed as such groups become permanently settled in a primary lived home away from the outsource of migration and simultaneously exhibit their inclusion in a life (of conspicuous consumption) from which many remaining residents are excluded.…”
Section: Diaspora Spaces In Punjabmentioning
confidence: 89%
“…Research in Uganda, which is probably indicative, showed that private capital flows, which includes migrant remittances, commonly known as kyeyo , rose from US$ 443.7 million to US$ 661.9 million per year between 1999 and 2002 ( The New Vision , 2003). Additionally, research has shown that remittances can be much more than formally transmitted pecuniary assets, and consist also of goods, and informal transfers of goods and money which go unrecorded (Rodriguez, 1996; Puri and Ritzema, 1999; Clark and Drinkwater, 2001; Ballard 2002, Orozco, 2002; Bracking and Sachikonye, 2006).…”
Section: Current Remittance and Poverty Knowledgementioning
confidence: 99%
“…Ballard 2003;Gardner 1995) such as I saw in Prantapur. In migration studies, there have been numerous discussions of the visible transformations of space and the built environment (e.g.…”
Section: New Economic and Spatial Alignments Upon Returnmentioning
confidence: 99%